PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT WAHANA KALYANA MITRA MAHARDIKA JAKARTA UTARA - Submission JORAPI; Ridwan; Hadi Winata (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the influence of motivation and physical work environment on employee performance at PT Wahana Kalyana Mitra Mahardika. The research method used is quantitative descriptive method. The sampling technique uses saturated sampling and obtained a sample of 50 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The result of this study is that work motivation has a significant effect on employee performance with a coefficient of determination value of 47.6% and the hypothesis test obtained t calculate > t table or (6.601> 2.011). The physical work environment also has a significant effect on employee performance with a coefficient of determination value of 62.0% and the hypothesis test obtained t calculate > t table or (8.841 > 2.011). Work motivation and physical work environment simultaneously have a significant effect on the performance of employees